Company Value: Disclosure Implications of Sustainable Supply Chian, Profitability and Industrial Profile - Dewi Anggraini; Putri Renalita Sutra Tanjung (International Journal of Supply Chain Management, 2020)
Abstract- The success of your business is inextricably linked to the productivity of your supply chain. This study aims to analyze the effect of Sustainable supply chian, Profitability and Industry Profile on Company Value. The sampling technique used was purposive sampling. The research was conducted on companies that are consistently included in the SRI KEHATI Index on the Indonesia Stock Exchange with a research period of 3 (three) years (2016-2018). The model estimation used is multiple regression analysis. The purpose of this study is to determine whether Sustainable supply chain Report, Profitability and Industry Profile have an influence on company value. The results of this study are Sustainable supply chain Report and Profitability affect the company value in accordance with Agency Theory and Stakeholder Theory. But the industry profile does not affect the company value.